2016
DOI: 10.1021/acs.jpca.5b10384
|View full text |Cite
|
Sign up to set email alerts
|

A New Nitrogenase Mechanism Using a CFe8S9 Model: Does H2 Elimination Activate the Complex to N2 Addition to the Central Carbon Atom?

Abstract: A truncated model of the FeMo cofactor is used to explore a new mechanism for the conversion of N2 to NH3 by the nitrogenase enzyme. After four initial protonation/reduction steps, the H4CFe8S9 cluster has two hydrogen atoms attached to sulfur, one hydrogen bridging two iron centers and one hydrogen bonded to carbon. The loss of the CH and FeHFe hydrogens as molecular hydrogen activates the cluster to addition of N2 to the carbon center. This unique step takes place at a nearly planar four-coordinate carbon ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 68 publications
6
48
1
Order By: Relevance
“…Recent computational studies propose that the carbide could even engage in covalent bonding with the N atoms during the N 2 reduction. 126,127 …”
Section: Carbide Complexes and Fe-n2 Complexes With Carbon Ligandsmentioning
confidence: 99%
“…Recent computational studies propose that the carbide could even engage in covalent bonding with the N atoms during the N 2 reduction. 126,127 …”
Section: Carbide Complexes and Fe-n2 Complexes With Carbon Ligandsmentioning
confidence: 99%
“…3 The experimental studies have been supplemented by many density functional theory (DFT) studies, which can give an detailed atomistic and energetic picture of the reaction mechanism. 3,[13][14][15][16][17][18][19][20][21][22][23][24][25][26] Unfortunately, they have led to strongly diverging mechanistic suggestions. For example, some studies have proposed that N 2 is sequentially protonated first on one N atom, which dissociates into NH 3 before the second atom is protonated, 23,25 whereas other studies have suggested that it is alternatively protonated on the two N atoms, forming N 2 H 2 and N 2 H 4 intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…side-on to one Fe ion, 22 with one N atom bridging two Fe ions, after the dissociation of one of the sulfide ions, 23 in the centre of the cluster, displacing a triply protonated carbide ion, 24 or forming a covalent bond to the carbide ion. 25,26 In fact, there is not even any consensus regarding the structure of the central intermediate E 4 . For example, Hoffman and coworkers have proposed models with two protonated sulfide ions and two bridging hydride ions, 27 in agreement with spectroscopic results, whereas Siegbahn has argued that it is energetically much more favourable to triply protonate the central carbide ion.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is no consensus in the detailed mechanism of the enzyme. For example, during 2015 and 2016 one group has suggested that N 2 binds side‐on to one Fe ion and is then protonated alternatively on the two N atoms, another that N 2 binds after the dissociation of one of the sulfide ions with one N atom bridging two Fe ions, and the non‐coordinating N atom is fully protonated and dissociates before the other N atom is protonated, whereas three groups have suggested that the central carbide ion is involved in the mechanism, either by receiving the incoming protons, or by covalently binding the N 2 substrate in various ways . A recent study addressed the role of His‐195 in the reaction mechanism…”
Section: Introductionmentioning
confidence: 99%
“…bridging two Fe ions, and the non-coordinating N atom is fully protonated and dissociates before the other N atom is protonated, [15] whereas three groups have suggested that the central carbide ion is involved in the mechanism, either by receiving the incoming protons, [16] or by covalently binding the N 2 substrate in various ways. [17,18] A recent study addressed the role of His-195 in the reaction mechanism. [19] The QM studies of nitrogenase are obstructed by the complicated nature of the FeMo cluster.…”
mentioning
confidence: 99%